2021
DOI: 10.3390/medicina57090866
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Circulating miR-497 and Metadherin in Hepatocellular Carcinoma: Relation to the Tumor Characteristics and Patients’ Survival

Abstract: Objectives: This study aimed to evaluate the prognostic significance and relationship of miR-497 and metadherin to hepatocellular carcinoma (HCC) tumor characteristics and patients’ survival. Methods: This study enrolled 120 (60 HCC patients and 60 healthy) subjects. Serum miR-497 and metadherin mRNA relative expression were analyzed by real-time quantitative reverse transcription polymerase chain reaction. The overall survival (OS) of HCC patients was assessed using the Kaplan–Meier curve and log-rank test. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…After removing 31 duplicate articles, the remaining 128 articles were screened according to inclusion and exclusion criteria, and 21 full-text articles were further reviewed. Finally, 6 studies with NOS scores greater than 6 were included after detailed screening [13,[17][18][19][20][21]. HR and 95% CI of two studies were extracted from the survival curve according to the method provided by Jayne F.T et al Te six included studies were all published between 2016 and 2021, including 457 patients.…”
Section: Features Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing 31 duplicate articles, the remaining 128 articles were screened according to inclusion and exclusion criteria, and 21 full-text articles were further reviewed. Finally, 6 studies with NOS scores greater than 6 were included after detailed screening [13,[17][18][19][20][21]. HR and 95% CI of two studies were extracted from the survival curve according to the method provided by Jayne F.T et al Te six included studies were all published between 2016 and 2021, including 457 patients.…”
Section: Features Of the Included Studiesmentioning
confidence: 99%
“…Tus, the role of miR-497 in the prognosis of patients with HCC has attracted much attention. Some studies have shown that the low expression level of miR-497 is signifcantly correlated with the poor prognosis of HCC [13,[17][18][19][20][21]. However, these studies have their limitations, such as small sample sizes or controversial results.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies showed that MTDH was abnormally expressed in various cancers, including esophageal, breast, gastric, liver cancer, osteosarcoma, and others. 84 89 In HCC cells, MTDH expression was significantly higher than that in adjacent nontumor tissues. Pathologically, MTDH level was positively correlated with pathologic satellites, advanced TNM stages and MVI ( p <0.001).…”
Section: Biomarkers Related To MVImentioning
confidence: 99%